A Study on Acetylglutamine Pharmacokinetics in Rat Blood and Brain Based on Liquid Chromatography-Tandem Mass Spectrometry and Microdialysis Technique - Xu, Shouchao; Li, Chang; Zhou, Huifen; Yu, Li; Deng, Ling; Zhu, Jiazhen; Wan, Haitong; He, Yu (Frontiers in Pharmacology, 2020)
Acetylglutamine (NAG) is the derivative of glutamine, which is the richest free amino acid in the human body. In this work, a novel reliable method of the combination of liquid chromatography-tandem mass spectrometry (LC-MS/MS) and microdialysis (MD) technique for evaluation of NAG and its metabolites γ-aminobutyric acid (GABA) and glutamic acid (Glu) in rat blood and brain was proposed. An Agilent Zorbax SB-C18 column (2.1×100 mm i.d., 3.5μM particle) was applied to separate the analytes. The mobile phase was acetonitrile-water (70:30, v/v) containing 5mM ammonium acetate and the flow rate was 0.3 mL/min. Based on the multiple reactions monitoring (MRM) mode of positive ion, the precursors of product ions chosen for NAG, Glu, GABA and N-carbamyl-L-glutamic (NCG, IS) were (m/z) 189.1→130.0, 148.0→84.1, 104→87.1 and 191.0→130.1, respectively. All the validation data, including precision, accuracy, inter-day repeatability, matrix effects and stability, were within the acceptable ranges. Rats with microdialysis probes in jugular venous and hippocampus were received tail vein injection of low (75mg/kg), medium (150mg/kg), and high (300mg/kg) doses of NAG and 10 mL/kg GHI, respectively. In the blood test, the Cmax values of NAG-L group were markedly lower (P<0.01) than those of NAG-M, NAG-H and Guhong injection (GHI) groups, respectively. No remarkable difference was observed between NAG-M and GHI groups, while the Cmax values in GHI group were significantly upgraded when compared with NAG-H group. There were notably differences in the Cmax values of NAG in brain dialysate after administration of NAG and GHI. The drug distribution coefficients of NAG, Glu, GABA in brain and blood in low, medium, high (50 ng/mL, 500 ng/mL, 5000 ng/mL) doses of NAG and GHI groups were 13.99, 27.43, 34.81, 31.37; 11.04%, 59.07%, 21.69%, 2.69%; 212.88%, 234.92%, 157.59% and 102.65%, respectively. Our investigation demonstrates that NAG and its related metabolites in rat blood and brain can be simultaneously measured according to the above proposed method. Meanwhile, NAG has easy and dose-dependently access to the blood-brain barrier and exhibits a medium retention time in rat.